Telmisartan Induced Myotoxicity - Rajesh Hadia; Rahul Trivedi; Cyril Sajan; Varunsingh Saggu; Sunil Baile; Sunil Kardani; Hemraj Singh Rajput (Novel Aspects on Pharmaceutical Research Vol. 3, 2023)
Drug-induced myopathy, a disease in which taking certain drugs can weaken or destroy muscles. Although the prevalence of this illness brought on by the drug Telmisartan is unknown, it is known that 150 different pharmaceuticals, including statins, corticosteroids, anti-retroviral treatments, and immunosuppressants, have been linked to myotoxicity. Guidelines advise therapeutic drug monitoring, which is routinely evaluating the levels of the medication in a patient’s circulation, to manage the risk of drug-induced myopathy linked to Telmisartan. Additionally, it should be highlighted that using Telmisartan is tolerated with a minimal rise in blood creatinine, a chemical produced by muscle tissue, of up to 20–30%. However, it is advised to stop the therapy if the serum creatinine level rises by more than 30%. The case described in the paragraph involves a patient who was thought to have experienced an adverse drug response (ADR) to the hypertension treatment Telmisartan. The ADR with Telmisartan was determined to be "Probable" after conducting a causality analysis utilising Naranjo’s algorithm and the WHO-UMC Scale. As a result, the drug was removed and replaced with Enalapril. The new drug helped the patient’s condition, and subsequent lab testing revealed that the patient’s levels of uric acid and creatinine were both within normal ranges. The chapter focuses on how crucial it is to closely monitor pharmacological therapy, especially when it involves prolonged use, in order to protect patients. Myotoxicity, a rare but serious adverse drug reaction, was the specific ADR connected to the drug Telmisartan in this instance. To prevent additional toxicity, Telmisartan was not administered to the patient again.